2018
DOI: 10.1016/j.ihj.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

A study to explore the factors related to treatment seeking delay among adults diagnosed with acute myocardial infarction at KMCH, Coimbatore

Abstract: ObjectiveThe main aim of the study was to explore the factors causing delay in seeking treatment among adult patients diagnosed with CAAs acute myocardial infarction (AMI) and compare the factors between timely and late treatment seeking groups.MethodA total of 93 subjects were included in the study diagnosed with AMI interviewed within 48 h of hospitalization. Data were collected from onset of symptoms to arrival at hospital on demography, clinical profile, clinical factors, cognitive factors and social suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
4
9
0
Order By: Relevance
“…Previous studies found that patients who reported an increased pain intensity were less likely to arrive late to a hospital. 31,34,36 Similarly, the current study found that patients who had higher pain scale scores were less likely to arrive late to the hospital. This might be due to that patients with severe pain perceived their condition more serious.…”
Section: Variablesupporting
confidence: 67%
“…Previous studies found that patients who reported an increased pain intensity were less likely to arrive late to a hospital. 31,34,36 Similarly, the current study found that patients who had higher pain scale scores were less likely to arrive late to the hospital. This might be due to that patients with severe pain perceived their condition more serious.…”
Section: Variablesupporting
confidence: 67%
“…In agreement with our findings, atypical symptoms, such as fatigue and non-chest pain, were reported as significant predictors for pre-hospital delays ( 9 , 11 ). Atypical symptoms were frequently perceived as benign and non-cardiac in origin ( 24 ), hence the lack of urgency to seek treatment earlier in a hospital. Our society may be aware of typical angina symptoms, such as crushing retrosternal chest pain with classical Levine’s sign, but many still lack awareness regarding atypical presentations that may occur, especially among females and among diabetic patients with neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Decision making time significantly depends on patients’ cognitive factors and their intuitive understanding about myocardial infarction. Inadequate knowledge may lead to the patients’ misinterpreting their own symptoms, subsequently furthering delay in decision making for seeking proper treatment ( 24 ). Our study found that patients who perceived their symptoms as cardiac in origin had significantly shorter symptom-to-door times ( P = 0.005).…”
Section: Discussionmentioning
confidence: 99%
“…This has been reported in other studies also where misinterpretation of symptoms was found to be a major factor responsible for pre hospital delays. [7][8][9][10][11][12] The other reason for delay in presentation could be the fact that many of our patients comes from hilly areas where traffic movement is slower. This was seen more so among females, where only 2 out of 20 females (10%) received treatment in first 2 hours compared to 15 of 80 (18.8%) men.…”
Section: Discussionmentioning
confidence: 99%
“…depending upon the social, cultural and local beliefs particularly in India where there is wide variation in these practices. [5][6][7][8][9][10][11][12] Our hospital caters to a quiet varied population coming from hilly and far flung rural areas where the educational, socioeconomic and health awareness level of people is quiet variable and transportation is sometimes a big issue. Therefore, this study was planned to assess the factors leading to delays in presentation and treatment and to evaluate its impact on the short term outcome.…”
mentioning
confidence: 99%